2018
DOI: 10.5152/eurjrheum.2018.18074
|View full text |Cite
|
Sign up to set email alerts
|

Association of soluble TREM-like transcript-1 with clinical features and patient reported outcomes in systemic lupus erythematosus

Abstract: ObjectiveThe soluble triggering receptor expressed on myeloid cells (TREM-1)-like transcript 1 (sTLT-1) has a modulatory effect on the activation of TREM-1. We compared plasma sTLT-1 levels between patients with systemic lupus erythematosus (SLE) and healthy individuals and determined the association between sTLT-1 levels and clinical features and patient-reported outcomes (PROs) among patients with lupus.MethodsAn unmatched case-control study was conducted in 46 patients with SLE and 28 healthy subjects. sTLT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Based on the critical role in immune, inflammation and platelets, previous studies of TLT-1 are mainly focused on these associated diseases. In patients with systemic lupus erythematosus, the soluble TLT-1 levels were significantly lower than healthy individuals [ 30 ]. In a model of acute lung injury, results showed that infusion of sTLT-1 restored normal fibrinogen deposition and alleviated pulmonary hemorrhage by 40% and tissue damage by 25% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the critical role in immune, inflammation and platelets, previous studies of TLT-1 are mainly focused on these associated diseases. In patients with systemic lupus erythematosus, the soluble TLT-1 levels were significantly lower than healthy individuals [ 30 ]. In a model of acute lung injury, results showed that infusion of sTLT-1 restored normal fibrinogen deposition and alleviated pulmonary hemorrhage by 40% and tissue damage by 25% [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 Previously, we reported that patients with systemic lupus erythematosus (SLE) had significantly lower levels of soluble TLT-1 (sTLT-1) when compared to healthy individuals. 2 Thus, we thought to determine if lower sTLT-1 levels are associated with the presence of anti-TLT-1 antibodies in SLE patients and if anti-TLT-1 antibodies are linked with SLE clinical features.…”
mentioning
confidence: 99%
“…Anti-TLT-1 antibodies were measured by enzyme-linked immunosorbent assay (ELISA) from stored plasma samples of the same SLE patients and healthy individuals that we previously reported and using sTLT-1 developed in-house. 1 , 2 The ELISA was developed according to Pierangeli and Harris. 3 Among SLE patients, we examined associations of anti-TLT-1 antibodies with demographic factors, SLE manifestations (per 1997 American College of Rheumatology (ACR) modified classification criteria), pharmacologic profile, comorbidities, disease activity (per the revised SLE activity measure (SLAM-R)), and the disease damage (per Systemic Lupus International Collaborating Clinics Damage Index).…”
mentioning
confidence: 99%